Simulation and Testing for Vehicle Technology 7th Conference, Berlin, May 12-13, 2016 - Gühmann, Clemens; Riese, Jens.; von Rüden, Klaus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book includes contributions on the latest model-based methods for the development of personal and commercial vehicle control devices. The main topics treated are: application of simulation and model design to development of driver assistance systems; physical and database model design for engines, motors, powertrain, undercarriage and the whole vehicle; new simulation tools, methods and optimization processes; applications of simulation in function and software development; function and software testing using HiL, MiL and SiL simulation; application of simulation and optimization in application of control devices; automation approaches at all stages of the development process.
Keywords: Automotive engineering; Automotive Engineering